THE RIGHTS OF USUFRUCT AND EASEMENT IN POLAND AND CHINA - SKORUPSKA, Paulina (Comparative Legilinguistics, 2016)
In this paper the terminology concerning the usufruct and easement in Poland and China was compared. The research material was the second book of the Polish Civil Code (promulgated on 23th April 1965) and the Chinese Property Rights Law (promulgated on 16th March 2007). To conduct the study the method of comparison of comparable texts was applied. In many cases it is possible to use functional equivalents from legal acts for examined terms. However, some terms have different ranges of meaning or the terms are non-equivalent and then applying, for instance, descriptive equivalents, is necessary.